Cell-by-cell-based finite-control-set model predictive control for a single-phase cascaded H-bridge rectifier - Qi, Chen (2020)
The traditional finite-control-set model predictive control (FCS-MPC) method for a cascaded H-bridge (CHB) rectifier has two main issues: heavy computational burden and low steady-state current performance. In this paper, a novel FCS-MPC method has been proposed for a single-phase CHB rectifier. The proposed method solves the optimization problem of FCS-MPC for one cell by one cell, like a "pipeline." In the proposed method, the sampling period is divided into equal intervals by the number of cells. At the beginning of the first interval, the first cell selects its switching state to be applied. Then, the following cell selects its switching state to be applied at the beginning of next interval. Finally, the selected switching state of last cell will be applied at the beginning of the last interval. A cost function presenting the control objectives of common source current error and itself dc-link voltage error is evaluated for each cell. A single-phase three-cell CHB rectifier controlled by a DSpace DS1104 is tested and the experimental results show that a significant reduction in computational time, an improved steady-state current performance, and a comparable dynamic response are achieved in the proposed method in comparison with the traditional FCS-MPC method.